Effects of aspergillus oryzae extract (amaferm) on ruminal fibrolytic bacteria and in vitro fiber degradation - A. A. Beharka; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1991)
The effect of Amaferm on growth of pure cultures of ruminal cellulose-digesting, hemicellulose- digesting and pectin-digesting bacteria was determined. The addition of Amaferm to the growth medium increased the growth of Ruminococcus albus and Fibrobacter succinogenes. Amaferm had no effect on the growth of the other bacteria. Additionally, selective antimicrobial compounds were used to assess the influence of Amaferm on microbial contributions to in vitro fiber degradation. Amaferm appeared to stimulate fiber digestibility of only certain feedstuffs, and this increase in digestibility was attributed to its stimulation of bacterial activity. Amaferm did not appear to stimulate fungal activity.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Rumen; Fungal; Microbial feed additive; Growth; Fiber